Perkembangan Agribisnis Teh Selama Pandemi Covid – 19 di PTPN VIII Kebun Kertamanah, Pangalengan, Jawa Barat - Diva Maurizky; Ernah Ernah (Hasanuddin University, 2022)
PTPN VIII Kertamanah PTPN Plantation is a country’s company under the Ministry of State-Owned Enterprises that engaged in the production of tea which has a good reputation in West Java. However, national’s tea production was tending to decrease in these past months and even get worsen because of the Covid – 19 pandemics which also has an impact on the plantation sector. This study aims to determine the tea agribusiness performance, internal and external factors in the company, and decide the viable tea agribusiness development strategies. This research uses descriptive-qualitative design and study case research technique. In needs to explaining the tea agribusiness performance is done descriptively, meanwhile for finding the right developing strategy there needs to be a matrix analysis of IFAS, EFAS, IE, and SWOT. Based on the descriptive data analysis, the production input procurement subsystem supports the production / cultivation and processing subsystem. Furthermore, those two subsystems support the running of the marketing subsystem. The smooth activites of all subsystems are supported by several supporting institutuions. The SWOT analysis resulted nine alternative strategies as like: (1) Mantaining performance and quality, (2) Opening job labor, (3) Making an inovation, (4) Maximazing the use of technology, (5) Maximazing company’s assets, (6) Work together with government and counseller, (7) Making a more detailed plan, (8) Take advantage of the superior factory program, and (9) Increasing promotion as long as the interesting education.